2023
DOI: 10.3390/cells12121581
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in CKD

Abstract: Chronic kidney disease (CKD) affects many adults worldwide. Persistent low-grade inflammation is a substantial factor in its development and progression and has correlated with increased mortality and cardiovascular problems. This low-grade inflammation is a product of dysregulation of the normal balance between pro- and anti-inflammatory markers. Various factors such as increased innate immune system activation, reactive oxygen species production, periodontal disease, dysregulation of anti-inflammatory system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…These in vivo observations are in full agreement with our previous in vitro data, demonstrating in PTEC that NLRP2 overexpression upregulates the expression and production of many proinflammatory and profibrotic genes by modulating the activity of the transcription factor NF-κB ( 19 ). Indeed, it has been widely demonstrated that the local production of inflammatory mediators by hematopoietic and non-hematopoietic cells, including Cxcl1 , Saa1 , Il6 and Mcp1 , which we found modulated in cystinotic kidney by Nlrp2 deletion, plays an important role in promoting immune and inflammatory responses which, in turn, may contribute to the exacerbation of kidney damage ( 29 , 30 ). Contrary to results obtained in vitro showing a role for NLRP2 in promoting anti-apoptotic responses in PTECs, Nlrp2 deficiency in cystinotic mice induced a significant decrease in renal apoptotic rate, as assessed by cleaved Caspase-3 staining.…”
Section: Discussionmentioning
confidence: 57%
“…These in vivo observations are in full agreement with our previous in vitro data, demonstrating in PTEC that NLRP2 overexpression upregulates the expression and production of many proinflammatory and profibrotic genes by modulating the activity of the transcription factor NF-κB ( 19 ). Indeed, it has been widely demonstrated that the local production of inflammatory mediators by hematopoietic and non-hematopoietic cells, including Cxcl1 , Saa1 , Il6 and Mcp1 , which we found modulated in cystinotic kidney by Nlrp2 deletion, plays an important role in promoting immune and inflammatory responses which, in turn, may contribute to the exacerbation of kidney damage ( 29 , 30 ). Contrary to results obtained in vitro showing a role for NLRP2 in promoting anti-apoptotic responses in PTECs, Nlrp2 deficiency in cystinotic mice induced a significant decrease in renal apoptotic rate, as assessed by cleaved Caspase-3 staining.…”
Section: Discussionmentioning
confidence: 57%
“…During dialysis, contact between blood and foreign objects can lead to acute and chronic in ammatory reactions through complement activation, cytokine or nitric oxide (NO) production, oxidant stress, carbonyl stress, activation of T-cell, B-cell and monocyte et al [16]. In addition, MHD patients can also experience sustained in ammatory activation due to factors such as oxidative stress, hypoxia, uid and sodium overload, dysbiosis of gut microbiota, and uremic toxins including indoxyl sulphate [6,17]. High levels of in ammation in MHD patients can further mediate the occurrence of depression through cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease is frequently accompanied by a persistent, low-grade inflammatory state, implicated in disease progression and linked to a spectrum of comorbid conditions including atherosclerosis, cardiovascular diseases, cachexia, malnutrition, and anemia [ 53 ]. At the core of this inflammatory milieu is IL-17A, a cornerstone cytokine within the IL-17 family, renowned for its proinflammatory actions in synergy with cytokines like IL-1-β and TNF.…”
Section: Discussionmentioning
confidence: 99%